A novel bifunctional additive for 5 V-class, high-voltage lithium ion batteries. Issue 9 (18th January 2016) - Feng, Jinkui; Gao, Xueping; Ci, Lijie; Xiong, Shenglin
Abstract : A novel additive is investigated as a bifunctional electrolyte additive for 5 V-class lithium ion batteries. Abstract : A novel additive is investigated as a bifunctional electrolyte additive for 5 V-class lithium ion batteries. It was found that the additive can be electro-polymerized at 5.05 V ( vs. Li/Li + ), which would protect the batteries from voltage runaway. Moreover, this additive could lower the electrolyte's self-extinguishing time (SET). The influence of this additive on cycling performance and capacity is positive, which makes it promising.